KONTRIBUSI RETRIBUSI PARKIR TERHADAP PENDAPATAN ASLI DAERAH PEMERINTAH KABUPATEN PACITAN - Sulastiningsih Sulastiningsih; Hasanah Setyowati; Mada-o Puteh; Yulyana Edin Saputri (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
The purpose of this study was to determine (1) the growth of parking retribution receipts from 2016 to 2020, (2) the effectiveness and efficiency of parking retribution receipts from 2016 to 2020, (3) the contribution of parking retribution receipts to PAD from 2016 until 2020. This type of research is descriptive qualitative. Data obtained by conducting interviews and documentation. Data analysis techniques used are quantitative analysis techniques and qualitative analysis techniques. The results of data analysis show that (1) The growth of parking retribution revenue in Pacitan City in 2017 was 32.2%; in 2018 by 53.2%; this means that the growth is positive while in 2019 the growth was negative, namely only (14.6%), in 2020 53.4% (2) The effectiveness of parking retribution receipts in Pacitan City from 2016 to 2020 reached an average of 6.069% per year. year. This shows that the acceptance of parking fees in Pacitan City is not effective while the efficiency of parking retribution receipts in Pacitan City reaches an average of 35.1% per year. This shows that the receipt of parking fees in Pacitan City is efficient. The contribution of Parking Retribution Revenue to Regional Original Revenue is 77.19% in 2016 61.65% in 2017 76.41%, in 2018 80.68% while in 2019 it was 81.94%. In 2020 it was 85.27%, increasing every year.